A Comparative Study of Gender Diversity on Firm Value between Companies Listed on the Nairobi and Uganda Securities Exchange - Mukyala, Veronica; Rono, Lucy; Charles, Lagat (Eastern Journal of Economics and Finance, 2021)
The purpose of this study was to determine how inclusions of women in corporate boards affect the value of listed firms in Nairobi and the Uganda Securities Exchange. The study used a panel research design and the data was obtained through content analysis from audited financial statements spanning from 2012 to 2019 and only 48 firms from NSE and 12 firms from USE met the inclusion and exclusion criteria. The fixed and random models were used to test the hypothesis. Hausman test was used for model selection and the fixed effect model was selected over random effects. Results; results revealed board gender diversity of listed firms in USE was higher compared to NSE. Further results showed that board gender diversity significantly and positively affects the value of listed firms in USE, while insignificantly affect the value of listed firms in NSE. Board gender diversity in USE significantly affects the firm value, while board gender diversity in NSE insignificantly affects the firm value. It can be concluded firms with a higher proportion of women on the board of directors have high firm value. This study can highlight the importance of including/appointing women as the board of directors in improving the value of companies. As the practical contribution to enhancing firm value, management of the companies and the investors should champion for more women appointed in corporate boards.